PENGARUH CAMPURAN BAHAN KOMPOSIT DAN KONSENTRASI GLISEROL TERHADAP KARAKTERISTIK BIOPLASTIK DARI PATI KULIT SINGKONG DAN KITOSAN - Mirah Pradnya Dewi, I Gusti Agung Ayu; Admadi H, Bambang; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This study aims to 1) determine the effect of material composite and glycerol concentration towards bioplastic characteristics 2) determine the mixture of composite and glycerol concentrations to produce the best characteristics of bioplastic composite. This research used a factorial randomized block design with 2 factors. First factor was the mixture of cassava starch skin and chitosan (starch: chitosan) which was consisted of 3 levels: 3g : 2g ; 3.5g : 1.5g ; 4g : 1g. The second factor was glycerol concentration of 3 levels: 1%, 1.5%, and 2%. Data was analyzed by using ANOVA and continued with Duncan test. The results showed that interaction between treatments very significantly affected the tensile strength and elasticity. The interaction between treatments was significantly affected toward elongation and the ability of biodegradation. The composite mixture of starch : chitosan (4 g: 1 g) and 1.5% glycerol concentration was the best treatment with characteristic of tensile strength 0.39MPa, elongation 44.06%, elasticity 0.008MPa, biodegradability 66.61% and the morphological characteristics is porous, because chitosan fiber larger than starch. Keywords: bioplastics, composites , starch, chitosan, glycerol
Keywords: 56